What are Green Bonds? - World Bank (Washington, DC, 2015)
The explosive growth of green bonds in the capital markets is increasingly attracting attention from investors. This surge in interest has created a demand for accessible information on the green bond market. This primer was created in response to this demand and covers the principles of this relatively new financial instrument. The following intends to serve as a guide for those interested in better understanding the nature of green bonds. The content will aim to distinguish green bonds from other traditional financial instruments. It will also provide insight into the potential of green bonds to mobilize new sources of climate finance. This paper includes the following highlights: understanding bonds (chapter one); understanding green bonds (chapter two); and benefits and potential.